Development of diesel engines cooling system - Mohammad Naqib Amirul, Abdul Rashid (2012)
The current vehicle cooling system is using the water or water mixed with anti-freezing additive usually using ethylene glycol (EG) as the coolant in order to perform cooling process the circulating working fluids through the vehicle radiator. The project is carried out in demonstrating nearly similar condition for the actual condition. In this project, the heat transfer performance of distilled water and TiO2 nanofluids with varied volume concentration is compared in the similar condition of the actual condition of temperature at radiator inlet, which from 90 °C to 60 °C. In addition, fluid flow rate also varied to compare the effect of different flow rate which 12 and 15 LPM to the heat transfer performance. The project gives the result that nanofluids clearly enhance heat transfer compared to their own base fluid. In the condition given, the best heat transfer enhancement of about 36.6 % compared to the base fluids has been recorded. The result gives the meaning that the typical coolant is could be replaced with nanofluids in order to have thermal transfer enhancement.